Ewentualna nieważność decyzji organu administracji publicznej w wyniku skazania osoby pełniącej określoną funkcję - Szulc, Piotr (Studia Prawa Publicznego, 2019)
The article presents the reflections on the potential invalidity of an administrative decision of a public administrative body as a result of the conviction of a person performing a function for an offence under Polish law. Firstly, the author analyses the legal situation of a person convicted for an offence under the Election Code (Kodeks wyborczy), the Act on Self-Government Employees (Ustawa o pracownikach samorządowych) and the Labour Code (Kodeks pracy). He examines in detail the discrepancies between the three legislative acts which may influence the legal position of a convicted person. The conclusion is that a person with the final and valid judgment for intentional offence prosecuted by public indictment to a fine or to penalty of imprisonment retains a passive electoral right in the elections for the mayor, however it seems that under the Act on Self-Government Employees it will not be possible to establish an employment relationship with such a person to work in the capacity of a self-government employee based on election. Secondly, the author analyses the potential invalidity of administrative decisions issued by a person convicted for an offence. The two conditions that could be taken into account as grounds for declaring the invalidity of an administrative decision in the context of the conviction are: a lack of jurisdiction of the authority as a condition of declaring the invalidity of a decision and a gross breach of law as a condition of declaring invalidity of a decision. The analysis of the selected conditions leads to a conclusion that there are no grounds for declaring the invalidity of a decision, as the regulations on jurisdiction will not be breached and the decision will not be issued in gross breach of law. Therefore, even if one were to consider that under the Act on Self-Government Employees a given person cannot be a self-government employee, it seems that this does not prevent the issuance of administrative decisions.